Les promoteurs des associations de travailleurs, Russie tsariste et soviétique, 1905-1930. Contribution à l’histoire des socialismes dits « utopiques ». - Anna Safronova (Cahiers d’histoire.)
Based on archival and print sources, the article reconstructs the network of actors who constituted association socialism and places their ideas and practices in a broader socio-political context. This paper argues that the ideas and practices of associationist socialists influenced the policy decisions of the Bolsheviks, despite the fact that the latter did not recognize the legitimacy of the political ideas of their opponents. Those who advocated workers' associations as a means of workers' emancipation did not structure themselves into an autonomous social movement with a commonly accepted political label and a central organization. Despite their marginalized position, this network of actors contributed to the socio-economic construction of the new regime after 1917.